MOF-derived carbon nanotube packaged nickel and nickel diselenide composite electrode material and preparation method and application thereof

Through the preparation of MOF-derived carbon nanotube encapsulated nickel and nickel diselenide composite electrode materials, multiple problems in the preparation and electrochemical process of transition metal selenide materials are solved, achieving high efficiency and low cost preparation and excellent Supercapacitor performance.

CN119153242APending Publication Date: 2024-12-17SICHUAN AGRI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411318008.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the preparation process, existing transition metal selenide materials have problems such as high energy consumption, complex procedures, agglomeration, low component dispersion, impurity, and volume expansion, aggregation and powderization in electrochemical processes, resulting in their supercapacitors. The cycle performance in the process is poor.

Method used

The preparation method of MOF-derived carbon nanotube encapsulated nickel and nickel diselenide composite electrode material is used to react zinc salt and 2-methylimidazole in methanol to produce ZIF-8, which is then mixed with nickel salt, and then undergo ultrasonication, reflux, Calcination and selenization treatment form Ni@CNT/NiSe2 composite electrode material with a "carbon nanotube forest" morphology.

Benefits of technology

This method simplifies the preparation process, reduces costs, improves the morphological quality of the material, inhibits volume expansion and particle aggregation, improves electron transfer rates, and exhibits high specific capacity and excellent cycling performance in supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153242A_ABST
    Figure CN119153242A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF-derived carbon nanotube packaged nickel and nickel diselenide composite electrode material and a preparation method and application thereof, and belongs to the technical field of new materials. A zeolite-like imidazate skeleton compound ZIF-8 is used as a carbon source, nickel salt and selenium powder are respectively used as a nickel source and a selenium source, and the composite electrode material is obtained through chemical reflux, high-temperature calcination and chemical vapor deposition reaction. The preparation method provided by the invention is low in cost and simple in process, the obtained electrode material has a unique micro-nano structure, and the problems of volume expansion, particle aggregation, pulverization and low electron / ion migration rate of the transition metal selenide material in the electrochemical reaction process can be effectively solved. The prepared composite electrode material is applied to a supercapacitor and capacitive deionization, and respectively shows relatively high specific capacity and excellent Cu < 2 + > electrochemical adsorption characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and in particular relates to a MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material, and a preparation method and application thereof. Background Art

[0002] With the rapid depletion of fossil fuels and the increasingly serious energy crisis, the current society has put forward an urgent need for environmentally friendly, low-cost and high-efficiency energy conversion and advanced storage technologies. Supercapacitors, a new form of electrochemical energy storage devices, have attracted great attention in the fields of hybrid electric vehicles, consumer electronics and backup energy systems due to their advantages such as rapid charging and discharging, long cycle life, low toxicity, low cost and abundant raw materials.

[0003] The electrodes of supercapacitors are composed of electrode active materials, binders, conductive agents and current collectors, among which the electrode active materials are the key factors that determine the performance of supercapacitors. At present, carbon materials, metal oxides, metal sulfides and conductive polymers have been reported as electrode materials in the field of supercapacitors. Although the electrochemical performance of the above electrode materials can be greatly improved through structural design, it is still difficult to meet the requirements of market applications due to the limitations of their intrinsic properties. Transition metal selenide materials have received great attention in the field of electrochemistry due to their high specific theoretical capacity and narrow bandgap semiconductor properties.

[0004] However, the preparation of transition metal selenides still faces many difficulties, which can be summarized as follows: (1) The traditional synthesis method has high energy consumption and complex procedures, which makes it difficult to carry out large-scale production of transition metal selenides in a practical sense. (2) During the hydrothermal / solvothermal synthesis process, a large amount of selenium source is required, and the generated transition metal selenides often agglomerate, with a particle size of tens of nanometers (or even micrometers) and low component dispersion. (3) The prepared transition metal selenides are impure and contain a large amount of impurities. (4) The prepared transition metal selenides are prone to serious volume expansion, particle aggregation and pulverization during the electrochemical process. Summary of the invention

[0005] In view of the above-mentioned prior art, the present invention provides a MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material and its preparation method and application, so as to solve the problems of complicated preparation process of existing transition metal selenides, severe volume expansion, aggregation and pulverization, and poor cycle performance during the electrochemical process.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material, comprising the following steps: S1: dissolving zinc salt and 2-methylimidazole in a first solvent respectively to obtain solution A and solution B; S2: Add solution A to solution B under stirring, let stand at room temperature for 10-15 h after ultrasonication, then wash the product and vacuum dry it to obtain the carbon source ZIF-8; S3: dissolving the carbon source ZIF-8 and the nickel salt in the second solvent respectively to obtain solution C and solution D; mixing solution C and solution D, and obtaining solution E after ultrasonication; S4: reflux solution E at 75-85 °C for 2-5 h, collect the product, wash it, and vacuum dry it to obtain a precursor; S5: calcining the precursor at 900-1200 °C for 3-5 h in an inert atmosphere to obtain product A; S6: mixing product A with selenium powder in an equal amount, and then calcining the mixture at 300-400 °C for 2-4 h in an inert atmosphere to obtain product B; S7: In an inert atmosphere, heat the product B to 380-450 °C and keep it warm for 1-3 h to obtain a composite electrode material.

[0007] Based on the above technical solution, the present invention can also be improved as follows.

[0008] Furthermore, the zinc salt is Zn(NO3)2·6H2O, the first solvent is methanol; the concentration of solution A is 37~37.5 g / L; and the concentration of solution B is 40~42 g / L.

[0009] Furthermore, the volume ratio of solution A to solution B in S2 is 1:1.

[0010] Furthermore, the cleaning method in S2 is to mix the product with methanol and then centrifuge, and the number of cleaning times is 2 to 5 times; the vacuum drying temperature is 70 °C.

[0011] Furthermore, the nickel salt is Ni(NO3)2·6H2O, the second solvent is methanol; the concentration of solution C is 10 g / L; and the concentration of solution D is 150 g / L.

[0012] Furthermore, the mass ratio of carbon source ZIF-8 to Ni(NO3)2·6H2O in solution E was 5:3.

[0013] Furthermore, the cleaning method in S4 is to mix the product with methanol and then centrifuge, and the number of cleaning times is 2 to 5 times; the vacuum drying temperature is 70 °C.

[0014] The invention also discloses a MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material prepared by the preparation method.

[0015] The invention also discloses the use of the MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material in the preparation of supercapacitors.

[0016] The present invention also discloses the above MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material in removing Cu from wastewater. 2+ Application in.

[0017] The beneficial effects of the present invention are: 1. The preparation method provided by the present invention has abundant raw material sources, low price, easy operation, high safety, and is conducive to large-scale production.

[0018] 2. The composite electrode material Ni@CNT / NiSe2 prepared by the preparation method provided by the present invention has a good morphology, presenting a morphology similar to that of a "carbon nanotube forest", and some nickel particles are in situ encapsulated in carbon nanotubes, and NiSe2 is coated in carbon materials. This structure is beneficial for inhibiting the volume expansion and particle aggregation of transition metal selenides during the electrochemical process, and the "carbon nanotube forest" is beneficial for the transmission of electrons and improves the electron transmission rate.

[0019] 3. The Ni@CNT / NiSe2 electrode with a carbon nanotube forest-like structure prepared by the present invention exhibits high specific capacity, excellent cycle performance and excellent ion adsorption capacity when used in supercapacitors and capacitive deionization, and is an electrode material with great commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD characterization result diagram of the composite electrode material Ni@CNT / NiSe2; Figure 2 The SEM characterization results of the composite electrode material Ni@CNT / NiSe2 at different scales; Figure 3 It is the electrochemical performance test diagram of the composite electrode material Ni@CNT / NiSe2; wherein A is the cyclic voltammetry test diagram of the composite electrode material Ni@CNT / NiSe2, and B is the constant current charge and discharge test diagram of the composite electrode material Ni@CNT / NiSe2; Figure 4 The electrode material Ni@CNT / NiSe2 is Cu 2+ The electrosorption capacity test results. DETAILED DESCRIPTION

[0021] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.

[0022] Example 1 A MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material is prepared by the following steps: S1: Dissolve 2.79 g Zn(NO3)2·6H2O in 75 mL methanol to obtain solution A; dissolve 3.08 g 2-methylimidazole in 75 mL methanol to obtain solution B; S2: Slowly pour solution A into solution B under stirring, ultrasonicate at 300 W for 10 min, and then stand at room temperature for 12 h; wash the obtained product by centrifugation with methanol three times, and finally vacuum dry at 70 °C overnight to obtain the carbon source ZIF-8; S3: 200 mg ZIF-8 was added to 20 mL methanol solution and ultrasonicated at 300 W for 5 min to obtain solution C; 450 mg Ni(NO3)2·6H2O was added to 3 mL methanol solution and fully dissolved to obtain solution D; S4: Take 800 uL of solution D and add it to solution C, and ultrasonicate it at a power of 300 W for 5 min to obtain solution E; reflux solution E at 80 °C for 3 hours, wash the obtained product by centrifugation with methanol three times, and dry the washed product in vacuum at 70 °C overnight; S4: The dried product was placed in a tube furnace (argon atmosphere) and calcined at 1000 °C for 4 h to obtain product A; selenium powder and product A were mixed in a mass ratio of 1:1, the mixture was placed in a tube furnace (argon atmosphere), and selenization (vapor deposition) was performed at 350 °C for 3 h, and product B was obtained after cooling; S5: Place product B in a tubular furnace (argon atmosphere) and perform deselenium treatment at 400 °C for 2 h to obtain a composite electrode material (Ni@CNT / NiSe2).

[0023] Example 2 A MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material is prepared by the following steps: S1: Dissolve 2.79 g Zn(NO3)2·6H2O in 75 mL methanol to obtain solution A; dissolve 3.08 g 2-methylimidazole in 75 mL methanol to obtain solution B; S2: Slowly pour solution A into solution B under stirring, ultrasonicate at 300 W for 10 min, and then stand at room temperature for 10 h; wash the obtained product by centrifugation with methanol for 3 times, and finally vacuum dry at 70 °C overnight to obtain the carbon source ZIF-8; S3: 200 mg ZIF-8 was added to 20 mL methanol solution and ultrasonicated at 300 W for 5 min to obtain solution C; 450 mg Ni(NO3)2·6H2O was added to 3 mL methanol solution and fully dissolved to obtain solution D; S4: Take 800 uL of solution D and add it to solution C, and ultrasonicate it at a power of 300 W for 5 min to obtain solution E; reflux solution E at 75 °C for 5 hours, wash the obtained product by centrifugation with methanol three times, and dry the washed product in vacuum at 70 °C overnight; S4: The dried product was placed in a tube furnace (argon atmosphere) and calcined at 900 °C for 5 h to obtain product A; selenium powder and product A were mixed in a mass ratio of 1:1, the mixture was placed in a tube furnace (argon atmosphere), and selenization (vapor deposition) treatment was performed at 400 °C for 2 h, and product B was obtained after cooling; S5: Place product B in a tubular furnace (argon atmosphere) and perform deselenium treatment at 380 °C for 3 h to obtain a composite electrode material (Ni@CNT / NiSe2).

[0024] Example 3 A MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material is prepared by the following steps: S1: Dissolve 2.79 g Zn(NO3)2·6H2O in 75 mL methanol to obtain solution A; dissolve 3.08 g 2-methylimidazole in 75 mL methanol to obtain solution B; S2: Slowly pour solution A into solution B under stirring, ultrasonicate at 300 W for 10 min, and then stand at room temperature for 15 h; wash the obtained product by centrifugation with methanol for 3 times, and finally vacuum dry at 70 °C overnight to obtain the carbon source ZIF-8; S3: 200 mg ZIF-8 was added to 20 mL methanol solution and ultrasonicated at 300 W for 5 min to obtain solution C; 450 mg Ni(NO3)2·6H2O was added to 3 mL methanol solution and fully dissolved to obtain solution D; S4: Take 800 uL of solution D and add it to solution C, and ultrasonicate it at a power of 300 W for 5 min to obtain solution E; reflux solution E at 85 °C for 2 hours, wash the obtained product by centrifugation with methanol three times, and dry the washed product in vacuum at 70 °C overnight; S4: The dried product was placed in a tube furnace (argon atmosphere) and calcined at 1200 °C for 3 h to obtain product A; selenium powder and product A were mixed in a mass ratio of 1:1, the mixture was placed in a tube furnace (argon atmosphere), and selenization (vapor deposition) was performed at 300 °C for 4 h, and product B was obtained after cooling; S5: Place product B in a tubular furnace (argon atmosphere) and perform deselenium treatment at 450 °C for 1 h to obtain a composite electrode material (Ni@CNT / NiSe2).

[0025] Experimental example The MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode materials prepared in the above-mentioned embodiments have similar performances. The composite electrode material in the embodiment is taken as an example to illustrate its performance.

[0026] The composite electrode material Ni@CNT / NiSe2 was characterized by XRD and SEM by X-ray diffractometer and scanning electron microscope to determine its purity and morphology. The results are as follows: Figure 1 and Figure 2 As shown; the electrochemical performance of the prepared composite electrode material Ni@CNT / NiSe2 was tested, and the results are shown in Figure 3 shown.

[0027] from Figure 1 It can be seen that the XRD test results of the composite electrode material Ni@CNT / NiSe2 are consistent with the standard card, and it can be determined that it is pure phase Ni@CNT / NiSe2.

[0028] from Figure 2 It can be seen that Ni@CNT / NiSe2 has a "carbon nanotube forest" structure derived from MOF, and there is in-situ encapsulation of nickel particles in the carbon nanotubes. In addition, there is also a NiSe2 structure coated with carbon materials. These unique morphological structures can effectively inhibit the volume expansion of NiSe2 during the electrochemical process and inhibit the aggregation of nickel particles. At the same time, the "carbon nanotube forest" structure can effectively shorten the ion transmission path and increase the electron migration rate.

[0029] Figure 3 (A) and Figure 3 (B) are the cyclic voltammetry test graph and constant current charge-discharge test graph of the composite electrode material Ni@CNT / NiSe2. Figure 3 Obvious redox peaks can be seen in (A), indicating that the electrode material has good electrochemical reversibility. Figure 3 As can be seen in (B), at a current density of 1 A / g, the electrode material has a specific capacitance of 185.6 F / g. When the current density is increased to 8 A / g, it still has a specific capacitance of 144.9 F / g, and the electrode still has a capacity retention rate of 94.6% after 5000 charge-discharge cycles at a current density of 5 A / g, indicating that the material has good rate performance and stable performance.

[0030] The composite electrode material Ni@CNT / NiSe2 prepared in Example 1 was subjected to Cu 2+ The results of the electrosorption test are as follows: Figure 4 As shown, A is the copper ion adsorption capacity of the composite electrode material Ni@CNT / NiSe2 at different voltages, and B is the copper ion adsorption capacity of the composite electrode material Ni@CNT / NiSe2 at different concentrations. As can be seen from the figure, the copper ion adsorption capacity of the Ni@CNT / NiSe2 electrode material at 0.8 V, 1.0 V, and 1.2 V voltages in the waste liquid with a copper ion concentration of 50 mg / L is 38.2 mg / g, 77.3 mg / g, and 101.1 mg / g, respectively; the copper ion adsorption capacity of the composite electrode material Ni@CNT / NiSe2 at a voltage of 1V in 10 mg / L, 25 mg / L, 50 mg / L, and 100 mg / L copper ion solutions is 19.8 mg / g, 32.3 mg / g, 77.3 mg / g, and 100 mg / g, respectively. The test results show that the composite electrode material Ni@CNT / NiSe2 in the present invention has a high copper ion adsorption capacity and can effectively remove Cu in wastewater. 2+ .

[0031] In addition, the composite electrode material Ni@CNT / NiSe2 prepared in Example 1 was subjected to Cu 2+ The electrosorption capacity test shows that the electrode material has a specific capacitance of 146.2 F / g at a current density of 1 A / g. When the current density is increased to 8 A / g, it still has a specific capacitance of 67.8 F / g, and the electrode still has a capacity retention rate of 85.2% after 5000 charge-discharge cycles at a current density of 5 A / g, indicating that the material has good rate performance and stable performance.

[0032] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments and drawings, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.

Claims

1. A method for preparing a MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material, characterized in that: The following steps are involved: S1: dissolving zinc salt and 2-methylimidazole in a first solvent respectively to obtain solution A and solution B; S2: Add solution A to solution B under stirring, let stand at room temperature for 10-15 h after ultrasonication, then wash the product and vacuum dry it to obtain the carbon source ZIF-8; S3: dissolving the carbon source ZIF-8 and the nickel salt in the second solvent respectively to obtain solution C and solution D; mixing solution C and solution D, and obtaining solution E after ultrasonication; S4: reflux solution E at 75-85 °C for 2-5 h, collect the product, wash it, and vacuum dry it to obtain a precursor; S5: calcining the precursor at 900-1200 °C for 3-5 h in an inert atmosphere to obtain product A; S6: mixing product A with selenium powder in an equal amount, and then calcining the mixture at 300-400 °C for 2-4 h in an inert atmosphere to obtain product B; S7: In an inert atmosphere, heat the product B to 380-450 °C and keep it warm for 1-3 h to obtain a composite electrode material.

2. The preparation method according to claim 1, characterized in that: The zinc salt is Zn(NO3)2·6H2O, the first solvent is methanol; the concentration of solution A is 37-37.5 g / L; the concentration of solution B is 40-42 g / L.

3. The preparation method according to claim 2, characterized in that: The volume ratio of solution A to solution B in S2 is 1:

1.

4. The preparation method according to claim 1, characterized in that: The cleaning method in S2 is to mix the product with methanol and then centrifuge it, and the number of cleaning times is 2 to 5 times; the vacuum drying temperature is 70 °C.

5. The preparation method according to claim 1, characterized in that: The nickel salt is Ni(NO3)2·6H2O, the second solvent is methanol; the concentration of solution C is 10 g / L; the concentration of solution D is 150 g / L.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the carbon source ZIF-8 to Ni(NO3)2·6H2O in the solution E is 5:

3.

7. The preparation method according to claim 1, characterized in that: The cleaning method in S4 is to mix the product with methanol and then centrifuge it, and the number of cleaning times is 2 to 5 times; the vacuum drying temperature is 70 °C.

8. The MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material according to claim 8 in the preparation of supercapacitors.

10. The MOF-derived carbon nanotube-encapsulated nickel and nickel diselenide composite electrode material of claim 8 is used to remove Cu from wastewater. 2+ Application in.